Variantnost govorjenega jezika v sociolingvističnih raziskavah - Bitenc, Maja (Jezik in slovstvo, 2025)
The article highlights the importance of comprehensive studies on spoken language, and presents various sociolinguistic research projects on language variation in Austria, Germany, Belgium, and Hungary. It focuses on the selection of informants, contexts of data collection, data analysis methods, the broader sociolinguistic context, and main findings. The described projects can serve as a starting point for planning further research on Slovene materials, addressing the expressed need for a more comprehensive understanding of the variation and change in spoken Slovene, and the relationship between language and society in the contemporary context.
Keywords: Dutch; German; Hungarian; jezikovna variantnost; jezikovne spremembe; language change; language variation; madžarščina; nemščina; nizozemščina; sociolinguistics; sociolingvistika